How sleep disorders affect patients with Alzheimer's disease - Costa, Juliana Ciarlini; Cardoso, Gleiry Yuri Rodrigues; Lima, Matheus Eugênio de Sousa; Aragão, Gislei Frota; Bachur, Tatiana Paschoalette Rodrigues (Revista Brasileira de Educação e Saúde, 2021)
Sleep disorders are common in patients with Alzheimer's disease. These disorders are highly related to the cognitive impairment and have as main risk factor the time of disease. Additionally, they can damage the patient’s quality of life, as well as their family’s and caregivers’. The aim of this study was to clarify which changes in sleep patterns occur in patients with Alzheimer's disease and how they occur. This narrative literature review was performed using five databases: MEDLINE, LILACS, Web of Science, Scopus, and Science Direct. Search terms were: Alzheimer’s disease, sleep-wake disorders, and dyssomnias. The research included articles published between 2000 and 2018, written in English, Portuguese and Spanish. Results showed that Alzheimer's disease is related mainly to REM sleep alterations, day-time sleepiness and napping, increased sleep fragmentation, and other less frequent disorders, such as decreased sleep efficiency and total sleep time, breathing disorders, and increased motor activity. Deposition of β-amyloid protein is the main pathophysiological substrate of sleep disorders, combined with increased orexin levels due to cholinergic deterioration in the central nervous system, and elevation of serum proinflammatory cytokines, associating circadian alterations with neuroinflammation. Therefore, sleep disorders are an important comorbidity in Alzheimer's disease, and can present in several ways, impairing the quality of life of these patients. The pathophysiological mechanisms of these comorbidities have not yet been fully elucidated, and further research that seeks to explain all these gaps is warranted.